Sarcoma Metabolomics: Current Horizons and Future Perspectives - Miguel Esperança-Martins; Isabel Fernandes; Joaquim Soares do Brito; Daniela Macedo; Hugo Vasques; Teresa Serafim; Luís Costa; Sérgio Dias (Cells, 2021)
The vast array of metabolic adaptations that cancer cells are capable of assuming, not only support their biosynthetic activity, but also fulfill their bioenergetic demands and keep their intracellular reduction–oxidation (redox) balance. Spotlight has recently been placed on the energy metabolism reprogramming strategies employed by cancer cells to proliferate. Knowledge regarding soft tissue and bone sarcomas metabolome is relatively sparse. Further characterization of sarcoma metabolic landscape may pave the way for diagnostic refinement and new therapeutic target identification, with benefit to sarcoma patients. This review covers the state-of-the-art knowledge on cancer metabolomics and explores in detail the most recent evidence on soft tissue and bone sarcoma metabolomics.